Observation of Spin Splitting in Room‐Temperature Metallic Antiferromagnet CrSb - Meng Zeng; Ming‐Yuan Zhu; Yu‐Peng Zhu; Xiang‐Rui Liu; Xiao‐Ming Ma; Yu‐Jie Hao; Pengfei Liu; Gexing Qu; Yichen Yang; Zhicheng Jiang; Kohei Yamagami; Masashi Arita; et al. (Advanced Science)
Abstract Recently, unconventional antiferromagnets that enable the spin splitting (SS) of electronic states have been theoretically proposed and experimentally realized, where the magnetic sublattices containing moments pointing at different directions are connected by a novel set of symmetries. Such SS is substantial, k‐dependent, and independent of the spin–orbit coupling (SOC) strength, making these magnets promising materials for antiferromagnetic spintronics. Here, combined with angle‐resolved photoemission spectroscopy (ARPES) and density functional theory (DFT) calculations, a systematic study on CrSb, a metallic spin‐split antiferromagnet candidate with Néel temperature TN = 703 K, is conducted. The data reveal the electronic structure of CrSb along both out‐of‐plane and in‐plane momentum directions, rendering an anisotropic k‐dependent SS that agrees well with the calculational results. The magnitude of such SS reaches up to at least 0.8 eV at non‐high‐symmetry momentum points, which is significantly higher than the largest known SOC‐induced SS. This compound expands the choice of materials in the field of antiferromagnetic spintronics and is likely to stimulate subsequent investigations of high‐efficiency spintronic devices that are functional at room temperature.